The use of authentic material by teachers to enhance the reading skill of students of Advanced Intensive English I from the Foreign Languages Department, University of El Salvador, semester II, year 2014 - Amaya Rodas, Claudia Verónica
This document contains valuable information about the undergraduate research work “The use of authentic materials by teachers to enhance the Reading skill of students of Advanced Intensive English I.” This investigation was carried out from April 2014 to December 2014. It provides detailed information on the use of authentic materials by teachers in the improvement of the reading skill to the advanced level ́ students of Licenciatura en Idioma Inglés opción Enseñanza at the Foreign Language Department in the Main Campus of the University of El Salvador during the semester II, year 2014.